Enalapril for severe heart failure in infancy. Issue 2 (February 1989) - Frenneaux, M; Stewart, R A; Newman, C M; Hallidie-Smith, K A
Abstract : Eight infants aged between 4 days and 12 weeks with severe heart failure that was refractory to optimal conventional treatment with diuretics were treated with enalapril. The starting dose was 0.1 mg/kg/day, increasing according to response to 0.12-0.43 mg/kg/day. One infant with severe myocarditis did not tolerate enalapril because of hypotension and later died of intractable heart failure. Six of the remaining patients had congenital systemic to pulmonary shunts and one had a simple aortic coarctation. Two weeks after starting enalapril the clinical features of heart failure had improved in all the infants, the mean (SEM) plasma sodium concentration had increased from 129 (2.4) to 136 (1.1) mmol/l and plasma urea concentration had fallen from 7.0 (0.85) to 2.9 (0.85) mmol/l. These data suggest that enalapril is a potentially useful treatment for severe heart failure in infancy.